Alzheimer's disease: insights from Drosophila melanogaster models. - Moloney, A.; Sattelle, D.B.; Lomas, D.A.; Crowther, D.C. (Trends in Biochemical Sciences, 2010)
The power of fruit fly genetics is being deployed against some of the most intractable and economically significant problems in modern medicine, the neurodegenerative diseases. Fly models of Alzheimer's disease can be exposed to the rich diversity of biological techniques that are available to the community and are providing new insights into disease mechanisms, and assisting in the identification of novel targets for therapy. Similar approaches might also help us to interpret the results of genome-wide association studies of human neurodegenerative diseases by allowing us to triage gene "hits" according to whether a candidate risk factor gene has a modifying effect on the disease phenotypes in fly model systems.